2009
DOI: 10.1038/nmat2432
|View full text |Cite
|
Sign up to set email alerts
|

Electric modulation of conduction in multiferroic Ca-doped BiFeO3 films

Abstract: Many interesting materials phenomena such as the emergence of high-Tc superconductivity in the cuprates and colossal magnetoresistance in the manganites arise out of a doping-driven competition between energetically similar ground states. Doped multiferroics present a tantalizing evolution of this generic concept of phase competition. Here, we present the observation of an electronic conductor-insulator transition by control of band-filling in the model antiferromagnetic ferroelectric BiFeO3 through Ca doping.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
356
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 497 publications
(376 citation statements)
references
References 40 publications
11
356
2
Order By: Relevance
“…22 According to the Nernst-Einstein relation, we note that the diffusivity of V O 2 þ can vary by many orders of magnitude for the typical activation energy of B1.0 eV of various perovskite oxides. 23,24 In Figures 5a and c, we show that the single-domain switching and the related photovoltaic characteristics remained qualitatively unchanged, regardless of the E-field poling temperatures. We only observed a small increase in I ph at 300 K. In the multidomain channel, however, domain reversal became notably inhomogeneous at 77 K, as shown in Figure 5b, leading to the absence of photovoltaic characteristics, as shown in Figure 5d.…”
Section: Resultsmentioning
confidence: 87%
“…22 According to the Nernst-Einstein relation, we note that the diffusivity of V O 2 þ can vary by many orders of magnitude for the typical activation energy of B1.0 eV of various perovskite oxides. 23,24 In Figures 5a and c, we show that the single-domain switching and the related photovoltaic characteristics remained qualitatively unchanged, regardless of the E-field poling temperatures. We only observed a small increase in I ph at 300 K. In the multidomain channel, however, domain reversal became notably inhomogeneous at 77 K, as shown in Figure 5b, leading to the absence of photovoltaic characteristics, as shown in Figure 5d.…”
Section: Resultsmentioning
confidence: 87%
“…In a previous study, we found that n-type-doped area of BFO by control of oxygen vacancies reveal prominently lower electronic conduction when compared with p-type doping areas. 33 It is likely that La 3 þ ions substitute Bi 3 þ ions (A-site doping) because they have similar effective ionic radii (1.36 Å ). 34 Although the La substitutions would modify structural and ferroelectric properties such as domain size, coercive voltage and fatigue behavior, 35,36 in many cases only the La 5% substitutions do not cause dramatic changes in physical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Oxygen vacancies generated during the deposition of Ba 0.7 Sr 0.3 TiO 3 are likely the charge traps. 26 This effect should exist in most oxide-based MIM devices, though it may not be the dominating factor. Further investigation using planar MIM devices should lead to a better understanding of the resistive switching phenomona.…”
Section: Copyright 2012 Author(s) This Article Is Distributed Under mentioning
confidence: 99%